2011
DOI: 10.1088/0029-5515/51/7/073033
|View full text |Cite
|
Sign up to set email alerts
|

Real-time control of the safety factor profile diagnosed by magneto-hydrodynamic activity on the Tore Supra tokamak

Abstract: Real-time control is essential for many aspects of tokamak operation. A key parameter to control is the current profile, since both confinement properties and magneto-hydrodynamic (MHD) activity depend on it in quite a sensitive way. The long pulse capability of the Tore Supra tokamak has allowed a unique type of experiment, where successive stationary states of the safety factor profile, defined by their MHD activity, are established and controlled in real time. Multiple target stationary states could be requ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…At the end of each P LH plateau the current profile has reached its stationary state. Several experiments have been carried out on Tore Supra to demonstrate the capability of this control scheme to obtain a desired stationary q-profile state and to sustain it in spite of preset variations of other plasma parameters such as plasma density, ion cyclotron resonant heating (ICRH) power or total current [14]. Successful experiments have been carried out featuring…”
Section: Rt Control Of Stationary States Of the Current Profilementioning
confidence: 99%
“…At the end of each P LH plateau the current profile has reached its stationary state. Several experiments have been carried out on Tore Supra to demonstrate the capability of this control scheme to obtain a desired stationary q-profile state and to sustain it in spite of preset variations of other plasma parameters such as plasma density, ion cyclotron resonant heating (ICRH) power or total current [14]. Successful experiments have been carried out featuring…”
Section: Rt Control Of Stationary States Of the Current Profilementioning
confidence: 99%
“…So, it leads to 19) is established. ✷ Theorem 1 Consider the error system (16) with the above assumptions and let (16) be driven by controller (17). Then the closed-loop system ( 18) is globally exponentially stable with respect to the induced norm .…”
Section: Disturbance-free Stabilizationmentioning
confidence: 99%
“…The closed-loop control of one single shape parameter, based on Single Input -Single Output (SISO) semi-empirical modelling, has been experimentally achieved (e.g control of plasma internal inductance [30] or non-inductive current drive profile width [3]). More recently, stationary states of the safety factor profile, defined by their MHD activity, were feedback controlled on Tore Supra [17]. However this is clearly not enough to match the main requirements of MHD stability and/or internal transport barriers issues [10].…”
Section: Introductionmentioning
confidence: 99%
“…During the development of combined LH/IC scenarios, it was confirmed that the IC power had a stabilizing effect [5]. In several instances, accidental IC power switch-off have occurred, resulting in the triggering of MHD activity.…”
mentioning
confidence: 91%